Childhood adversity, externalizing behavior, and substance use in adolescence: Mediating effects of anterior cingulate cortex activation during inhibitory errors. (October 2019) - Fava, Nicole M.; Trucco, Elisa M.; Martz, Meghan E.; Cope, Lora M.; Jester, Jennifer M.; Zucker, Robert A.; Heitzeg, Mary M.
Abstract: Childhood adversity can negatively impact development across various domains, including physical and mental health. Adverse childhood experiences have been linked to aggression and substance use; however, developmental pathways to explain these associations are not well characterized. Understanding early precursors to later problem behavior and substance use can inform preventive interventions. The aim of the current study was to examine neurobiological pathways through which childhood adversity may lead to early adolescent problem behavior and substance use in late adolescence by testing two prospective models. Our first model found that early adolescent externalizing behavior mediates the association between childhood adversity and alcohol, cigarette, and marijuana use in late adolescence. Our second model found that activation in the anterior cingulate cortex (ACC) during an inhibitory control task mediates the association between childhood adversity and early adolescent externalizing behavior, with lower ACC activation associated with higher levels of adversity and more externalizing behavior. Together these findings indicate that the path to substance use in late adolescence from childhood adversity may operate through lower functioning in the ACC related to inhibitory control and externalizing behavior. Early life stressors should be considered an integral component in the etiology and prevention of early and problematic substance use.